1997
DOI: 10.1172/jci119624
|View full text |Cite
|
Sign up to set email alerts
|

High expression of the chemokine receptor CCR3 in human blood basophils. Role in activation by eotaxin, MCP-4, and other chemokines.

Abstract: Eosinophil leukocytes express high numbers of the chemokine receptor CCR3 which binds eotaxin, monocyte chemotactic protein (MCP)-4, and some other CC chemokines. In this paper we show that CCR3 is also highly expressed on human blood basophils, as indicated by Northern blotting and flow cytometry, and mediates mainly chemotaxis. Eotaxin and MCP-4 elicited basophil migration in vitro with similar efficacy as regulated upon activation normal T cells expressed and secreted (RANTES) and MCP-3. They also induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
274
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(286 citation statements)
references
References 44 publications
9
274
0
3
Order By: Relevance
“…Chemokine receptor (CCR)3 is a common receptor to all three chemokines 29, its expression is up regulated in AD lesions 30, and its blockade by monoclonal antibodies inhibits eosinophils recruitment 31. CCR3 is also expressed on basophils 32, mast cells 33, and activated Th2 cells 34. Therefore, honey's significant down regulation of IL4‐induced CCL26 release by keratinocytes could explain, at least partly, our clinical findings.…”
Section: Discussionmentioning
confidence: 84%
“…Chemokine receptor (CCR)3 is a common receptor to all three chemokines 29, its expression is up regulated in AD lesions 30, and its blockade by monoclonal antibodies inhibits eosinophils recruitment 31. CCR3 is also expressed on basophils 32, mast cells 33, and activated Th2 cells 34. Therefore, honey's significant down regulation of IL4‐induced CCL26 release by keratinocytes could explain, at least partly, our clinical findings.…”
Section: Discussionmentioning
confidence: 84%
“…In BM, we observed that also CCR3 dim cells, which according to studies in mice may represent immature eosinophils [19], were EMR1 + . Notably, while CCR3 and Siglec-8 are also expressed by basophils [20,21], EMR1 was absent on basophils and thus is a highly specific marker for eosinophils in humans (Fig. 2E, Table 1).…”
Section: Eosinophilic Granulocytes Express Emr1mentioning
confidence: 99%
“…Eotaxin/CCL11 is a member of the CC chemokine family that has potent chemotactic activity for eosinophils (15,16), basophils (17), mast cells (18), and Th2-type lymphocytes (19). Eotaxin/ CCL11 protein is up-regulated in a variety of inflammatory diseases possessing an eosinophilic component, such as allergic asthma (20,21), chronic sinusitis (22), and allergic rhinitis (23), and is thought to be a key player in the pathogenesis of these conditions.…”
mentioning
confidence: 99%